An Epidemiological Approach of Hydrocephaly Parameters in Duhok Province - Alsuf, saad (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): This study was conducted to deal with the importance and effect of various variables which mighthave influence in hydrocephaly occurrence.Methodology: A retrospective design was performed and continued for 4 months. It included 89 nonrandomizedconsecutive samples collected from the Early Detection of Childhood Disabilities Center (E.D.C.D.C.)Duhok. The population involved was the entire cases of both sexes that attended the centre during the period from1st.Jan, 1998 to 30th. Dec. 2008 with final diagnosis of hydrocephaly. Patients’ records from the centre were used tocollect data.Results: Hydrocephaly has been recognized as a public health problem in Duhok province, Iraqi Kurdistan region,many aspects of which still remain unclear. The results indicated that males mainly suffer (53.9%), highestoccurrence of hydrocephaly cases occur in summer (42.7%), patients aged 7-10 years were the highest (55.1%),consanguious parents constitute (57.3%), mother's age group of 26-35 years had the highest occurrence (56.2%),deliveries conducted in hospitals (85.4%), Duhok city showed the highest incidence (61.8%), normal deliveries werethe highest (83.1%) and finally idiopathic cases were (39.3%).Recommendations: It is highly recommended to establish hydrocephaly screening units in all maternityhospitals in Duhok province and discouragement of consanguineous marriages.